Improving the Quality of Technology Teacher Training in the Context of Edu 5.0: Analyzing AI Application Trends and Proposing Curriculum Improvements - Phan Nguyễn Trúc Phương; Bùi Văn Hồng; Đinh Văn Đệ (Journal of Technical Education Science, 2025)
In the current context, artificial intelligence (AI) is creating profound changes in many fields, especially education. This study focuses on the impact of AI technology on technology teacher training programs. Through a comprehensive analysis of published international articles, we assess the development trends of AI in education and its effects on teacher training. The results show that AI is significantly changing content, teaching methods, and assessment. This requires training programs to be updated to equip students with necessary skills in the digital age. Based on the research results, we propose specific measures to supplement the learning outcomes for technology teacher training programs in Vietnam, including integrating AI knowledge, developing skills in applying AI in teaching, and enhancing adaptability to new technologies. This study provides an important basis for improving training programs, contributing to enhancing the quality of technology teacher training according to the AI ​​application trend.